The Impact of Green Supply Chain Management On Sustainable Performance: Mediated By Green Supplier Integration, Green Customer Integration, and Proactive Environmental Strategy - Bramadi Theodorus Wijaya; Gede Ariadi (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: Indonesia is progressing toward sustainability by promoting green supply chain management (GSCM) practices among businesses. Despite their potential to improve environmental performance, farmers remain hesitant due to perceived complexity, high cost, and the need for operational adjustments. Purpose: This research investigates how green supplier integration, customer integration, and proactive environmental strategies mediate the relationship between GSCM practices and sustainable performance. The goal is to identify ways to make GSCM more accessible and advantageous for farmers. Design/Methodology/approach: The research employs a quantitative approach using Smart PLS-3, a structural equation modelling tool, to analyze the relationships between GSCM practices, integration strategies, and sustainable performance. Data were collected from farmers in Cuntel Village, Kopeng. Finding/result: The study found that GSCM does not directly influence sustainable performance but works through mediating variables. Green supplier integration is the potent mediator, followed by green customer integration and proactive environmental strategy, which enhance GSCM’s impact on sustainability. Conclusion: Collaborative efforts between suppliers, customers, and farmers, combined with forward-looking environmental strategies, can make GSCM practices more practical and effective. These approaches address the skepticism of farmers by demonstrating tangible benefits and reducing implementation complexities. Originality/value (State of the art): The research provides a unique perspective on mediating factors that bridge the gap between GSCM practices and sustainable performance. It offers actionable insights for policymakers, businesses, and farmers, aligning GSCM practices with Indonesia’s sustainable development goals. Keywords: green supply chain management, sustainable performance, green supplier integration, green customer integration, proactive environmental strategy